Exceptional preservation of a prehistoric human brain from Heslington, Yorkshire, UK - O’Connor, Sonia; Ali, Esam; Al-Sabah, Salim; Anwar, Danish; Bergström, Ed; Brown, Keri A.; Buckberry, Jo; Buckley, Stephen; Collins, Matthew; Denton, John; Dorling, Konrad M.; Dowle, Adam; et al. (Journal of archaeological science, 2011)
Archaeological work in advance of construction at a site on the edge of York, UK, yielded human remains of prehistoric to Romano-British date. Amongst these was a mandible and cranium, the intra-cranial space of which contained shrunken but macroscopically recognizable remains of a brain. Although the distinctive surface morphology of the organ is preserved, little recognizable brain histology survives. Though rare, the survival of brain tissue in otherwise skeletalised human remains from wet burial environments is not unique. A survey of the literature shows that similar brain masses have been previously reported in diverse circumstances. We argue for a greater awareness of these brain masses and for more attention to be paid to their detection and identification in order to improve the reporting rate and to allow a more comprehensive study of this rare archaeological survival. ► Survival of a prehistoric brain in an excavated skull. ► Exceptional ceremonial deposit. ► Characterisation of the composition of the preserved brain. ► Critical review of brain survival in skeletalised human remains back to the 18th century. ► Investigation of conditions for brain preservation.